Characterizing the genetic evolution of endemic bluetongue virus strains - Kopanke, Jennifer H., author; Mayo, Christie, advisor; Callan, Rob, committee member; Ebel, Greg, committee member; VandeWoude, Sue, committee member (Colorado State University. Libraries, 2019)
Bluetongue virus is an arthropod-borne virus that can cause severe disease in susceptible animals. Transmitted by biting midges in the genus Culicoides, the bluetongue virus particle (genus Orbivirus, family Reoviridae) is composed of ten segments of double-stranded RNA enclosed by a bi-layered, icosahedral capsid. While both wild and domestic ruminants are capable of becoming infected with bluetongue virus, sheep are most likely to develop severe disease characterized by systemic vasculitis, edema, and coagulopathy. Due to its relatively unusual genome structure, bluetongue virus (BTV) is able to evolve via several key mechanisms, including via the accumulation of mutations over time, or more rapidly via reassortment of genome segments. Adding to this genetic complexity, bluetongue virus must maintain fitness in two very disparate hosts: the insect vector and the ruminant. While host-switching is widely accepted as an important aspect of bluetongue virus evolution, the specific features of viral adaptation in each host are poorly characterized. Limited field studies and experimental work from other labs have alluded to the presence of these phenomena at work in the evolutionary trajectory of bluetongue virus, but our overall understanding of the factors that drive or constrain this virus's genetic diversification remains incomplete. In recent years, bluetongue virus has caused significant disease outbreaks among ruminants in enzootic regions, such as the U.S., as well as in areas where bluetongue virus was previously considered exotic, such as northern Europe. Various dynamics including vector range expansion, movement of animals, virus evolution through reassortment and mutation, and environmental factors all may have an integral role in the occurrence of these outbreaks. Not only do bluetongue epizootics carry sometimes profound animal health consequences, but they are also associated with significant economic impacts due to production declines, costly efforts to contain disease spread, and trade restrictions. Collectively, our currently limited understanding of bluetongue virus ecology and evolution dramatically hinders our ability to predict and prevent the occurrence of epizootics associated with orbiviruses. As whole genome sequencing approaches have become increasingly available and affordable, these tools provide a uniquely valuable platform for interrogating underlying viral genetic factors associated with bluetongue disease incursions and outbreaks. Coupling applied fieldwork, in vitro, and in vivo studies with sequencing tools and bioinformatics, the work described in this dissertation seeks to address specific knowledge gaps surrounding bluetongue evolution in North America. In particular, we first queried how an alternating-host transmission cycle affects bluetongue's genetic diversity using an in vitro system, where we leveraged whole genome sequencing and measures of population genetics to understand the role of viral mutation during BTV evolution. We found low rates of overall mutation, leading us to consider whether reassortment is a relatively greater contributor to bluetongue's genetic diversity. Once again using an in vitro platform, we investigated reassortment frequency and segment-specific trends between two enzootic bluetongue virus strains. Our work demonstrated that global shifts in segment frequencies emerged across serial passages, possibly representing preferred reassortant segment combinations. However, most viral segments persisted – even if at very low levels – within the overall population from passage to passage. To better characterize these trends, and to understand whether environmental factors such as temperature might affect their occurrence, we introduced these same viruses into Culicoides sonorensis midges – the predominant North American vector of bluetongue virus – and tracked virogenesis and reassortment across time at three different temperatures. Correlating with other studies, we found that higher temperatures were associated with more rapid virogenesis. However, we were surprised to find that one of the two virus strains replicated poorly in midges orally infected with biologically relevant titers, highlighting potential vector-based barriers to reassortment. Finally, we used whole genome sequencing to characterize circulating strains of bluetongue virus present in Colorado ruminants in 2015 and 2018. We found that numerous strains of bluetongue virus were present among sentinel animals, and that many isolates contained signatures of reassortment. Collectively, our findings demonstrate that reassortment among virus strains is a prominent feature of bluetongue viral evolution. Importantly, there appear to be preferred segment combinations that arise following coinfection, but vector-virus interactions seem to play a central role in modulating the ultimate emergence of reassortant viruses. These studies and others promise to improve our understanding of bluetongue's evolution and ecology, ultimately contributing to the development of better predictive models and management strategies to reduce future impacts of bluetongue epizootics.
Keywords: whole genome sequencing; evolution; bluetongue virus; reassortment; Culicoides; Orbivirus